Peranan Penyusunan Anggaran Biaya Produksi dalam Menunjang Efektivitas Pengendalian Biaya Produksi (Studi Kasus pada (PTPN X) Pabrik Gula Tjoekir, Jombang) - Neily Amalia; Dwi Ari Pertiwi (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
This study aims to improve to find out the planned production cost budget plant at Tjoekir Sugar Factory, and to know the effectiveness of controlling production costs. To ensure the results of this study, researchers will examine the planned production cost budget and its realization in three periods, from 2016 to 2018. In this study, researchers used a descriptive analytical approach. The data analysis used is qualitative analysis. And the data source used in this qualitative research is primary data and secondary data. Seeing the final results of this research and discussion the researchers concluded, that the effectiveness of controlling production costs at the Tjoekir Sugar Factory in 2016 had not been achieved, because in 2016 the production costs were still too much or exceeded the budget set by the Tjoekir Sugar Factory, which was 107.77 %. And for 2017 the control of production costs has been achieved very effectively, because production costs are lower than the stipulated budget, which is 91,37%. Whereas for 2018, cost control has also been achieved very effectively, because spending on production costs is far lower than the budget that has been laid, i.e. 86.27%.